A Survey of Tick Infestation on Cattle within Fulani Settlements of the University of Abuja Main Campus, F.C.T., Abuja - Yoila David, Malann,; Gywa, Deme, Gideon; Adetutu, Olanrewaju, Comfort; Adigun, Abdulkareem, K. (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2018)
Ticks have been noted as the main ectoparasites which reduces the cattle productivity in the tropics. The study investigated ticks of cattle among Fulani herds residents at the fringes of the  Main Campus of the University of Abuja. All the cattle examined in this study were free-ranged.  A total of 148 cattle were examined for tick infestation of which Amblyomma species was the most recorded 313(54.34%), other species that were found to occur in the study area were Hyalomma species, Boophilus species, and Rhipicephalus species with (25.35%, 13.72%, and  6.60%) respectively. All ticks species recorded were all from the family Ixodidae. The level of infestation of the tick in relation to sex and age showed significant difference (P<0.05). The study also showed male ticks smaller than the female in all species recorded. This investigation was necessary to give baseline information on the level of tick infestation and occurrence in the study area to increase public awareness especially to the herd men to avoid tick-borne diseases and also help in vector control formulations